2009
DOI: 10.1186/1477-7827-7-120
|View full text |Cite
|
Sign up to set email alerts
|

The role and molecular mechanism of D-aspartic acid in the release and synthesis of LH and testosterone in humans and rats

Abstract: D-aspartic acid is a physiological amino acid occurring principally in the pituitary gland and testes and has a role in the regulation of the release and synthesis of LH and testosterone in humans and rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
120
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 29 publications
(44 reference statements)
8
120
1
Order By: Relevance
“…The study concluded that DAA is involved in steroidogenesis. Additional studies using rodents have found similar results [100,49].…”
Section: Non-herbal Dietary Supplementssupporting
confidence: 69%
See 4 more Smart Citations
“…The study concluded that DAA is involved in steroidogenesis. Additional studies using rodents have found similar results [100,49].…”
Section: Non-herbal Dietary Supplementssupporting
confidence: 69%
“…The study concluded that DAA is involved in steroidogenesis. Additional studies using rodents have found similar results [100,49].Studies of DAA involving human subjects are scarce. In the first published study, Topo and colleagues found that testosterone levels were significantly elevated in response to DAA supplementation [49].…”
supporting
confidence: 58%
See 3 more Smart Citations